Sustainable Tourism Implementation In Indonesia: Emphasizing Green Tourism, Community-Based Tourism, and Local Empowerment - Risfandini, Andini (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
Several crucial concepts are integral to the successful implementation of sustainable tourism practices in Indonesia. Among these, Green Tourism, Community Based Tourism, and Local Empowerment stand out as pivotal frameworks. Green tourism has promise as an environmentally friendly offering, although it requires a deeper understanding of environmentally conscious advancement within the tourism sector. At present, difficulties remain in delineating the notion of sustainable tourism and in implement it in tourism destinations. This study is filling the gap of the existing research on sustainable tourism by providing recommendations to enhance environmental sustainability practices by focusing on Green Tourism, Community Based Tourism and Local Empowerment. This article aims to explore these concepts in depth and highlight the best practices associated with each one. This research employs a qualitative methodology, specifically employing an integrative literature review approach to investigate the implementation of green tourism in Indonesia. In conclusion, sustainable tourism implementation in Indonesia is a complex and multifaceted process. It involves the active participation of local communities, the development of sustainable policies and plans, and the promotion of a green economy. Government engagement and community involvement are crucial for the successful implementation of sustainable tourism. To comprehensively examine the role of stakeholders and prioritize variables crucial for devising strategies in sustainable tourism implementation, further research utilizing a quantitative approach is recommended. Additionally, it is imperative to test the concept of step-by-step local empowerment using quantitative methods to ensure its validity.